Characterization and pre‐breeding of diverse alfalfa wild relatives originating from drought‐stressed environments. Issue 1 (22nd October 2020) - Humphries, Alan W.; Ovalle, Carlos; Hughes, Steve; del Pozo, Alejandro; Inostroza, Luis; Barahona, Viviana; Yu, Linqing; Yerzhanova, Sakysh; Rowe, Trevor; Hill, Jeff; Meiirman, Galiolla; Abayev, Serik; et al.
Abstract: Changing climates and associated increased variability pose risks to alfalfa ( Medicago sativa L.) cultivation, with the requirement to establish, survive, and maintain production under water stress. Crop wild relatives (CWR) of alfalfa include populations that have evolved to survive in a number of different, extreme environments, but until recently have had limited use in breeding programs. Here we report on the phenotypic diversity of alfalfa crop wild relatives that were selected to represent extremes in drought tolerance (by sourcing germplasm from environments with extremes in low rainfall, high temperature, shallow soils, and winter freezing) with the aim of providing germplasm with drought tolerance and improved forage yield traits for breeding programs in both warm and cool dry temperate environments. Newly formed hybrids created between M. sativa, M. arborea L. (a woody shrub), and M. truncatula Gaertn. (an annual species from the Mediterranean region) were developed or acquired to introduce new genetic diversity from the tertiary genepool. Preliminary characterization and evaluation was used for taxonomic classification, and to identify wild accessions and pre‐bred (hybrid) lines that offer new diversity for growth habit, seed size, fall dormancy, and forage yield. The accessions and pre‐breeding lines described have been donated to the Australian Pastures Genebank for conservation and distribution. Core Ideas: Crop wild relatives offer diversity for adaptation to extreme environments. Pre‐breeding with CWR can introduce new variability for forage yield and fall dormancy. Alfalfa x M. arborea hybrids offer new opportunities to improve seed size and forage yield.